2013
DOI: 10.1002/hep.26634
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus induced up-regulation of microRNA-27: A novel mechanism for hepatic steatosis

Abstract: MicroRNAs (miRNAs) are small RNAs that posttranscriptionally regulate gene expression. Their aberrant expression is commonly linked with diseased states, including hepatitis C virus (HCV) infection. Herein, we demonstrate that HCV replication induces the expression of miR‐27 in cell culture and in vivo HCV infectious models. Overexpression of the HCV proteins core and NS4B independently activates miR‐27 expression. Furthermore, we establish that miR‐27 overexpression in hepatocytes results in larger and more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…This subset of miRNAs included miR-122, which is a key player in HCV infection and liver disease (reviewed in reference 4); miR-21-5p, which has consistently been shown to be implicated in HCV infection and liver disease (47)(48)(49); and miR-146a-5p, a well-known immunoregulatory miRNA further described to be associated with liver fibrosis and HCC (54,55,(64)(65)(66). Moreover, members of the miR-27 family of miRNAs, which contribute to the regulation of lipid metabolism, were recently reported to be increased by HCV and to contribute to liver steatosis (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…This subset of miRNAs included miR-122, which is a key player in HCV infection and liver disease (reviewed in reference 4); miR-21-5p, which has consistently been shown to be implicated in HCV infection and liver disease (47)(48)(49); and miR-146a-5p, a well-known immunoregulatory miRNA further described to be associated with liver fibrosis and HCC (54,55,(64)(65)(66). Moreover, members of the miR-27 family of miRNAs, which contribute to the regulation of lipid metabolism, were recently reported to be increased by HCV and to contribute to liver steatosis (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ethanol feeding inhibits PPAR-α function due to the effect of acetaldehyde, which inhibits transcriptional activation of PPAR-α [91] . HCV causes down-regulation of PPAR-α [92] , and is able to inhibit its activity by inducing repression of PPAR-α signaling by micro RNA-27b [93] . Leptin, another fat-derived cytokine, may promote fibrogenesis through up-regulation of transforming growth factor-β [94] , but it also protects the liver from fat accumulation by lowering the expression of SREBP-1 [95] .…”
Section: Fat As An Endocrine Organ: Cytokinesmentioning
confidence: 99%
“…Typically, they repress target gene expression through effect on the mRNA stability or translation. To date, there is growing evidence and experimental studies which have specifically explored the involvement of miRNAs in the mechanism associated with NAFLD development by regulating corresponding genes [20,31]. For example, the results from our ongoing studies on potential gene targets using the target prediction algorithms and the pathway analysis tools have revealed that around 54 miRNAs regulate 107 genes involved in the pathogenesis of hepatic steatosis (unpublished data).…”
Section: General Progress Of Nafldmentioning
confidence: 94%